Implementation of Folktales Based on Bima Local Wisdom to Improve Reading Literacy of Grade 3 Students at MIS Nurul Ilmi, Bima City - Puput Anggriani; Abdussahid; Yayuk Kusumawati (Lembaga Bale Literasi, 2026)
This study aims to determine the application of the case method learning model in Civics learning to improve critical thinking skills of 5th grade students of SDN Inpres Padende. This type of research is Classroom Action Research. The results of the study concluded that the average evaluation results of cycle I were 81 with a classical completion percentage of 58%. While the average evaluation results of cycle II were 89 with a classical completion percentage of 92%. This means that the ideal classical completion target of 85% has been achieved. The percentage increase from cycle I to cycle II was 34%. The increase can also be seen from the results of the teacher activity observation sheet in cycle I, which was 74% with a fairly well implemented category and increased in cycle II to 89% and was categorized as well implemented. The percentage increase from cycle I to cycle II was 15%. Based on the conclusions that have been obtained; to improve the case method learning model, the researcher provides suggestions for teachers to be expected to innovate in implementing the learning process. The selection of learning methods must be adjusted to the characteristics of the material and student abilities. Teachers can develop methods that support the implementation of learning. Careful planning makes learning effective and efficient, thereby achieving learning objectives. Using more engaging learning methods will help students learn and understand the material, one example of which is the use of the case study method.